Dispachability improvement of wind generation by the Virtual Power Producers. (30th June 2008) - Morais, H.; Cardoso, M.; Saleiro, N.; Vale, Z.A.; Castanheira, L.; Praca, I.
Today, there is a growing environmental concern about where the energy that we use comes from, bringing the attention on renewable energies. However, the use and trade of the renewable energies in the market seem to be complicated because of the lack of guarantees of generation, mainly in the wind farms. The lack of guarantees is usually addressed by using a reserve generation. The aggregation of Distributed Generation plants gives place to a new concept: the Virtual Power Producer (VPP). VPPs can reinforce the importance of wind generation technologies, making them valuable in electricity markets. This paper presents some results obtained with a simulation tool (ViProd) developed to support VPPs in the analysis of their operation and management methods and of their strategies effects.